PENGARUH AIR PDAM, LAUT, COMBERAN PADA PROSES CURING TERHADAP KUAT TEKAN BETON Fc 14,53 Mpa - Richo Dwi Saputra; Rasio Hepiyanto (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2017)
Concrete is a mixture of concrete forming materials, namely: fine aggregate, coarse aggregate, cement, and water. Each concrete construction always be able to show its function, ie strength and endurance during the planned life. Therefore, in this research concrete treatment is known to increase the concrete but also need to know how long the concrete treatment is good Only requires water from the loss of water experienced. Thus the research is conducted to find out how much the influence of curing process uses sea water, PDAM sewage toward to the strength of concrete press. This research was conducted with the use of 3 types of water that is water PDAM, sea water, sewage. Cylindrical tests specimen with diameter 15 cm and height 30 cm. Each sample is made of 3 specimens by the age of 7 days. The value of compressive strength in PDAM water, seawater, sewage successively at the age of 7 days is 13,522 MPa, 8,759 MPa, 10,296 MPa. The value of compressive strength of Water PDAM at 7 days has increased compared to the compressive strength value of seawater and sewage, while the value of compressive strength of seawater has decreased compared to the rising sewage. So it can be concluded that the value of the highest compressive strength is water PDAM at the age of 7 days.